Urgensi Penyelenggaraan Pelayanan Publik Ditinjau dari Peraturan Presiden Nomor 89 Tahun 2021 - Daud, Erita Rosa Larasati; Prasetyo, Ngesti Dwi; Susmayanti, Riana (Universitas Negeri Malang, 2025)
This study aims to identify the urgency of implementing a Public Service Mall in the context of Indonesian bureaucracy and the challenges of implementing it in light of Presidential Regulation Number 89 of 2021. This study used a normative juridical method with a descriptive qualitative approach, focusing on the analysis of secondary legal materials such as laws and regulations, official documents, and other legal literature. Data collection techniques in this study were conducted through library research. Data analysis in this study uses qualitative normative techniques to interpret legal provisions and examine their legal implications. The Public Service Mall is a strategic innovation aimed at improving the effectiveness, efficiency, and quality of public services. The implementation of the Public Service Mall in practice still faces various challenges, such as inter-agency coordination, infrastructure readiness, and service system integration. The success of the Public Service Mall requires ongoing commitment and synergy from all stakeholders to realize modern, transparent, and adaptive public services.